PERANCANGAN SISTEM INFORMASI KUNJUNGAN HARIAN PASIEN RAWAT JALAN DI UPT PUSKESMAS CIJERAH - Majiid, Nurul Salsasabilla; Dewi, Ayu Septiyana; Syahidin, Yuda; Setiatin, Sali (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2021)
Puskesmas is a health care facility that organizes public health efforts and first-level individual health efforts by prioritizing promotional and preventive efforts in its work area. Problems that occur in the recording of daily visits of outpatients in the Puskesmas are still done manually, so as not to close the possibility of mistakes in recording daily visits of patients. In addition, in making a monthly report the officer calculates one by one the number of patient visits on the day manually so that it takes a long time. The purpose of this study was to design the Patient Daily Visit Information System Program using Microsoft Visual Studio 2010 to make it easier for officers to record and report monthly. This research method uses the waterfall method. The final result of the design of this system resulted in the Patient's Daily Visit Information System using Microsoft Visual Studio 2010 which is expected to facilitate the recording and storage of daily visits of patients because it is computerized.